Analisis Pengetahuan Orang Tua terhadap Perkembangan Motorik Kasar pada Toddler - Dwi Erika Yanthi, Ni Kadek Ayu; Adven Christi Rihi Mone; Wahyu Sari, Ni Luh Made Reny (Pusat riset dan Inovasi Nasional, 2025)
Gross motor development in toddlers (aged 1–3 years) serves as a crucial foundation for their physical, cognitive, and social growth. Parental knowledge about the stages of this development is essential for providing appropriate stimulation and early detection of developmental delays. However, studies indicate that many parents, particularly in developing countries such as Indonesia, still have limited understanding, potentially hindering the optimal development of their children. This study aims to analyze parental knowledge of gross motor development in toddlers through a systematic literature review (SLR) of 20 selected studies conducted between 2020 and 2025. The findings reveal variability in parental knowledge levels, with education, access to digital information, and the role of healthcare professionals identified as key determinants. Recommended interventions include community-based education programs via posyandu (integrated health posts) for rural areas and the use of digital platforms for urban populations, supported by multisectoral policy integration to ensure program effectiveness and sustainability.